2009
DOI: 10.1111/j.1538-7836.2008.03215.x
|View full text |Cite
|
Sign up to set email alerts
|

African-American ethnicity is associated with higher plasma levels of D-dimer in adults with hypertension

Abstract: Summary. Background: African Americans with hypertension have higher cardiovascular morbidity and mortality than hypertensives from other ethnic groups. Plasma D-dimer, a fragment generated from fibrin during lysis of mature clot in vivo, is a predictor of adverse cardiovascular events. Objective: We investigated whether plasma levels of D-dimer differ between African American (AA) and non-Hispanic white (NHW) adults with hypertension. Methods: Participants included 933 AA (65 ± 9 years, 72% women) and 821 NHW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Some authors have demonstrated that hypertensive patients present higher levels of PAI-1 [13,14] and D-Di [15] compared to normotensive individuals. In addition, antihypertensives may decrease [9,16,17] or not interfere [10,18] on these biomarkers.…”
Section: Discussionmentioning
confidence: 98%
“…Some authors have demonstrated that hypertensive patients present higher levels of PAI-1 [13,14] and D-Di [15] compared to normotensive individuals. In addition, antihypertensives may decrease [9,16,17] or not interfere [10,18] on these biomarkers.…”
Section: Discussionmentioning
confidence: 98%
“…This increased susceptibility is not completely explained by the prevalence of traditional cardiovascular risk factors. Indeed, novel risk factors may play some role, at least in the development of vascular diseases such as PAD, possibly in the ethnic susceptibility to cardiovascular disease [17,28].…”
Section: Discussionmentioning
confidence: 99%
“…1517 However, the relationship of D-dimer to CVD events specifically in AAs has only been addressed in one recent study. 7 D-dimer levels are also higher in women than men, for unknown reasons.…”
Section: Introductionmentioning
confidence: 99%